Mechanistic aspects and therapeutic applications of RNAi - Rossi, John (Henry Stewart Talks, 2007)
RNAi mechanisms, RNAi and HIV infection, Lentiviral vector-mediated transduction of stem cells and T-cells, Gene therapy based treatment of HIV-1, HIV mutants that abrogate RNAi, Multiplexing different siRNAs and siRNAs with other antiviral RNAs to minimize viral resistance, An HIV Tat inducible shRNA expression system, Multiplexing shRNA with dominant negative M10 protein inhibition of HIV
Reviewed at 2015/08/21, Archived at 2022/03/27